A concept for international societally relevant microbiology education and microbiology knowledge promulgation in society - Timmis, K; Hallsworth, JE; McGenity, TJ; Armstrong, R; Colom, MF; Karahan, ZC; Chavarría, M; Bernal, P; Boyd, ES; Ramos, JL; Kaltenpoth, M; Pruzzo, C; et al. (Wiley, 2024)
Executive summary Microbes are all pervasive in their distribution and influence on the functioning and well-being of humans, life in general and the planet. Microbially-based technologies contribute hugely to the supply of important goods and services we depend upon, such as the provision of food, medicines and clean water. They also offer mechanisms and strategies to mitigate and solve a wide range of problems and crises facing humanity at all levels, including those encapsulated in the sustainable development goals (SDGs) formulated by the United Nations. For example, microbial technologies can contribute in multiple ways to decarbonisation and hence confronting global warming, provide sanitation and clean water to the billions of people lacking them, improve soil fertility and hence food production and develop vaccines and other medicines to reduce and in some cases eliminate deadly infections. They are the foundation of biotechnology, an increasingly important and growing business sector and source of employment, and the centre of the bioeconomy, Green Deal, etc. But, because microbes are largely invisible, they are not familiar to most people, so opportunities they offer to effectively prevent and solve problems are often missed by decision-makers, with the negative consequences this entrains. To correct this lack of vital knowledge, the International Microbiology Literacy Initiative–the IMiLI–is recruiting from the global microbiology community and making freely available, teaching resources for a curriculum in societally relevant microbiology that can be used at all levels of learning. Its goal is the development of a society that is literate in relevant microbiology and, as a consequence, able to take full advantage of the potential of microbes and minimise the consequences of their negative activities. In addition to teaching about microbes, almost every lesson discusses the influence they have on sustainability and the SDGs and their ability to solve pressing problems of societal inequalities. The curriculum thus teaches about sustainability, societal needs and global citizenship. The lessons also reveal the impacts microbes and their activities have on our daily lives at the personal, family, community, national and global levels and their relevance for decisions at all levels. And, because effective, evidence-based decisions require not only relevant information but also critical and systems thinking, the resources also teach about these key generic aspects of deliberation. The IMiLI teaching resources are learner-centric, not academic microbiology-centric and deal with the microbiology of everyday issues. These span topics as diverse as owning and caring for a companion animal, the vast range of everyday foods that are produced via microbial processes, impressive geological formations created by microbes, childhood illnesses and how they are managed and how to reduce waste and pollution. They also leverage the exceptional excitement of exploration and discovery that typifies much progress in microbiology to capture the interest, inspire and motivate educators and learners alike. The IMiLI is establishing Regional Centres to translate the teaching resources into regional languages and adapt them to regional cultures, and to promote their use and assist educators employing them. Two of these are now operational. The Regional Centres constitute the interface between resource creators and educators–learners. As such, they will collect and analyse feedback from the end-users and transmit this to the resource creators so that teaching materials can be improved and refined, and new resources added in response to demand: educators and learners will thereby be directly involved in evolution of the teaching resources. The interactions between educators–learners and resource creators mediated by the Regional Centres will establish dynamic and synergistic relationships–a global societally relevant microbiology education ecosystem–in which creators also become learners, teaching resources are optimised and all players/stakeholders are empowered and their motivation increased. The IMiLI concept thus embraces the principle of teaching societally relevant microbiology embedded in the wider context of societal, biosphere and planetary needs, inequalities, the range of crises that confront us and the need for improved decisioning, which should ultimately lead to better citizenship and a humanity that is more sustainable and resilient. Abstract The biosphere of planet Earth is a microbial world: a vast reactor of countless microbially driven chemical transformations and energy transfers that push and pull many planetary geochemical processes, including the cycling of the elements of life, mitigate or amplify climate change (e.g., Nature Reviews Microbiology, 2019, 17, 569) and impact the well-being and activities of all organisms, including humans. Microbes are both our ancestors and creators of the planetary chemistry that allowed us to evolve (e.g., Life's engines: How microbes made earth habitable, 2023). To understand how the biosphere functions, how humans can influence its development and live more sustainably with the other organisms sharing it, we need to understand the microbes. In a recent editorial (Environmental Microbiology, 2019, 21, 1513), we advocated for improved microbiology literacy in society. Our concept of microbiology literacy is not based on knowledge of the academic subject of microbiology, with its multitude of component topics, plus the growing number of additional topics from other disciplines that become vitally important elements of current microbiology. Rather it is focused on microbial activities that impact us–individuals/communities/nations/the human world–and the biosphere and that are key to reaching informed decisions on a multitude of issues that regularly confront us, ranging from personal issues to crises of global importance. In other words, it is knowledge and understanding essential for adulthood and the transition to it, knowledge and understanding that must be acquired early in life in school. The 2019 Editorial marked the launch of the International Microbiology Literacy Initiative, the IMiLI. Here, we present